Blood trimethylamine-N-oxide originates from microbiota mediated breakdown of phosphatidylcholine and absorption from small Intestine - Stremmel, Wolfgang; Schmidt, Kathrin V.; Schuhmann, Vera; Kratzer, Frank; Garbade, Sven; Langhans, Claus-Dieter; Fricker, Gert; Okun, Jürgen G. (PLOS ONE, 2017)
Elevated serum trimethylamine-N-oxide (TMAO) was previously reported to be associated with an elevated risk for cardiovascular events. TMAO originates from the microbiota-dependent breakdown of food-derived phosphatidylcholine (PC) to trimethylamine (TMA), which is oxidized by hepatic flavin-containing monooxygenases to TMAO. Our aim was to investigate the predominant site of absorption of the bacterial PC-breakdown product TMA. A healthy human proband was exposed to 6.9 g native phosphatidylcholine, either without concomitant treatment or during application with the topical antibiotic rifaximin, or exposed only to 6.9 g of a delayed-release PC formulation. Plasma and urine concentrations of TMA and TMAO were determined by electrospray ionization tandem mass spectrometry (plasma) and gas chromatography-mass spectrometry (urine). Native PC administration without concomitant treatment resulted in peak plasma TMAO levels of 43 ± 8 μM at 12 h post-ingestion, which was reduced by concomitant rifaximin treatment to 22 ± 8 μM (p < 0.05). TMAO levels observed after delayed-release PC administration were 20 ± 3 μM (p < 0.001). Accordingly, the peak urinary concentration at 24 h post-exposure dropped from 252 ± 33 to 185 ± 31 mmol/mmol creatinine after rifaximin treatment. In contrast, delayed-release PC resulted in even more suppressed urinary TMAO levels after the initial 12-h observation period (143 ± 18 mmol/mmol creatinine) and thereafter remained within the control range (24 h: 97 ± 9 mmol/mmol creatinine, p < 0.001 24 h vs. 12 h), indicating a lack of substrate absorption in distal intestine and large bowel. Our results showed that the microbiota in the small intestine generated the PC breakdown product TMA. The resulting TMAO, as a cardiovascular risk factor, was suppressed by topical-acting antibiotics or when PC was presented in an intestinally delayed release preparation.